L’hydrologie printanière de la rivière Saint-François - Cazalis, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1965)
The abundant spring run-off in Southern Québec is a result of the heavy winter precipitation and the length of the retaining period. One half of the annual discharge occurs in March, April and May, yet the maximum monthly coefficient (April) on the Saint-François is little more than 300. This low figure is due to the length of the thawing season, which extends the flood over at least four weeks, and to the retaining action of the numerous lakes. Occasionally a heavy spring rainfall may alter the character of the run-off, but even then there is never any question of spring flood damage to land or property — the river s are swollen rather than in flood. Critical conditions can arise however on the Saint-François following storm rains and rapid run-off (impermeability and steep slopes). The water rises rapidly, but the fall extends over a week. These floods are more severe than in spring, but damage is still minimal, the lakes in fact store 50% of the surface run-off and in the case of certain tributaries, 75%. Furthermore, the maximum specific discharge is not more than 20 cu. ft/sec/sq. m. for the regulated tributaries (Magog, Massawippï) compared with 80 or more for those that are not. Through the regulating influence of the main tributaries and that of the hydro-electric power dams on the Saint-François itself], the regime of the river is one of the most serene in Southern Québec.